Fostering Reading Skill on Narrative Text by Using Sticky Notes: Students’ Experiences in The Indonesian Higher Education Context - Sri Wahyuningsih; Alfina lailis Sa'adah (Universitas 17 Agustus 1945 Semarang, 2022)
The present study aims to find out how the use of sticky notes can help EFL students to improve their skills in reading narrative texts. Using a qualitative approach, data were collected through semi-structured interviews taking a sample of 7 third-semester EFL students at an Indonesian higher education. Interview data in the form of implementation patterns of using sticky notes in narrative texts were explored to determine recommendations and produce research. The findings of this study from qualitative research indicate that provocative language and plots are major contributors to EFL students' difficulties in reading narrative texts. In addition, it also shows that EFL students use various reading comprehension strategies. Based on the results of this study, a new approach was found using sticky notes to read narrative texts. Most of the participants considered the use of sticky notes to be effective in improving reading skills. Although there were, several participants, stated that their use was less effective for reasons of time efficiency. The impact of this research is that a new method, namely sticky notes which are considered commonplace, can provide benefits in improving students' reading skills in English.